2018
DOI: 10.1007/s11864-018-0525-1
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Treatment for Adults with Synovial Sarcoma

Abstract: Opinion StatementSynovial sarcoma (SS) is a rare, yet highly malignant, type of soft tissue sarcoma (STS), for which survival has not improved significantly during the past years. In this review, we focus on systemic treatment in adults. Compared to other STS, SS are relatively chemosensitive. Ifosfamide and ifosfamide combinations are active in different lines of treatment. In high-risk extremity and chest wall STS, neoadjuvant doxorubicin and ifosfamide has shown as much activity as high-dose ifosfamide. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
81
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 78 publications
0
81
0
1
Order By: Relevance
“…Previous studies reported metastases in 50% of those cases, while the 5-year survival is 60.5% (6,12,13). Additionally, some studies have shown a 10-year survival rate ranging between 24 and 68% (6,(12)(13)(14). The most common metastases are found in the lungs, followed by lymph nodes, bone and liver.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Previous studies reported metastases in 50% of those cases, while the 5-year survival is 60.5% (6,12,13). Additionally, some studies have shown a 10-year survival rate ranging between 24 and 68% (6,(12)(13)(14). The most common metastases are found in the lungs, followed by lymph nodes, bone and liver.…”
Section: Discussionmentioning
confidence: 95%
“…For cases with localized, low-risk disease treatment involves surgical resection and, in some cases, (neo)adjuvant radiotherapy (12). Previous studies reported metastases in 50% of those cases, while the 5-year survival is 60.5% (6,12,13). Additionally, some studies have shown a 10-year survival rate ranging between 24 and 68% (6,(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations